Zolpidem efficacy and safety in disorders of consciousness. (21st March 2018) - Machado, Calixto; Estévez, Mario; Rodriguez-Rojas, Rafael
ABSTRACT: Sutton and Clauss presented a detailed review about the effectiveness of zolpidem, discussing recoveries from brain damage due to strokes, trauma and hypoxia. A significant finding has been the unexpected and paradoxical increment of brain activity in vegetative state/unresponsive wakefulness syndrome (VS/UWS). On the contrary, zolpidem is considered one of the best sleep inducers in normal subjects. We have studied series of VS/UWS cases after zolpidem intake. We have demonstrated EEG activation, increment of BOLD signal in different brain regions, and an autonomic influence, mainly characterized by a vagolytic chronotropic effect without a significant increment of the vasomotor sympathetic tone. As this autonomic imbalance might induce cardio- circulatory complications, which we didn't find in any of our patients, we suggest developing future trials under control of physiological indices by bedside monitoring. However, considering that the paradoxical arousing zolpidem effect might be certainly related to brain function improvement, we agree with Sutton and Clauss that future multicentre and multinational clinical trials should be developed, but under control of physiological indices